Multi-carrier OFDM, Single Carrier with Frequency Domain Equalization (SCFDE) and CDMA: Performance Comparison - Buzid, T. M.; Eddaghel, M.; Belgassem, F. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The equalization in the frequency domain is common between multi-carrier OFDM and the single carrier with frequency domain equalization SCFDE systems as well as code division multiple access CDMA. Therefore, performances can be fairly compared. In this paper, we explain why the OFDM and CDMA systems demonstrate similar signal fluctuation as shown by simulation results in the literature. Furthermore, MC-CDMA, a combination of OFDM and CDMA is shown to be SCFDE; therefore, the same performance could be achieved with simpler instrumentation, and, the combination of SCFDE and CDMA is shown to be an OFDM system.